The Urgency of Professional Indemnity Insurance in Research and Innovation Practices in Indonesia - Yanti Permatasari; Elisatris Gultom; Edi Hilmawan (Green Publisher Indonesia, 2024)
This study explores the importance of legal protection for researchers in Indonesia, particularly in the context of professional indemnity insurance. It highlights the risks faced by researchers in their work, such as potential failures in research and innovation, and examines the legal framework that mandates protection for researchers under Indonesian law. Despite the legal provisions, the study identifies a gap in the implementation of protective policies, which hinders the effective safeguarding of researchers' rights. By comparing best practices from developed and developing countries, the research offers insights into how Indonesia can improve its legal protection for researchers, emphasizing the potential role of professional insurance as a viable solution.